Editorial: International Journal of Architectural Engineering Technology - Lee, Kyung Hoon (International Journal of Architectural Engineering Technology, 2014)
Welcome to the inaugural issue of International Journal of Architectural Engineering Technology. IJAET is a peer reviewed academic journal for propagation of practices based information on engineering and technical issues pertaining to all aspects of building design and construction. Our aim is to publish most complete and reliable source of information on the discoveries and current developments in this area through original articles, review articles, short communications, etc. The journal provides a platform to facilitate the exchange of information between architects and engineers for technical advancement globally. The four papers in our inaugural issue are on timely topics, and contain archival information and knowledge that would be useful to all readers. This Journal will publish editorials, original articles, letters related to every field of Architectural Engineering Technology. Avanti Publisher will also be showcased, since without their strong motivation and financial commitment, much of what has been accomplished would not have been possible. For this first issue of the Journal, it is indeed a great pleasure to be able to publish original research articles and reviews by authors from Spain, China, Turkey and Taiwan. This new Journal will undoubtedly serve as a continuous stimulus to basic and applied research in years to come. It is an honor and privilege for me to contribute to its launch and early development. I look forward to welcoming you to our community and sending our first issue containing reviews and research articles in the area of energy technology research.